PERKEMBANGAN PEMANFAATAN PLTS DI BANDAR UDARA DI DUNIA - Abid Surya Bimantara; I Nyoman Satya Kumara; Wayan Gede Ariastina (Program Studi Teknik Elektro UNUD, 2021)
Solar power plants in their application have reached the aviation business. There arealready many airports everywhere that use solar power plants as their electrical energy supply.Airports and airfields have a very high opportunity to accommodate solar technology because ofopen land space. The purpose of this research is to review the advantages or disadvantages ofairports solar power plants and conduct a survey of any airports in the world that already havesolar power plants. This research used data collected from journals, articles, and news on theinternet. Those data include airports that use solar power plants, solar power plantsestablishment year, airport category, airport location, airport solar power plants capacity, solarpower plants type. Hence, the review describes the advantages and disadvantages of PLTSand its specific site everywhere. The results show that 192 airports already use PLTS as anelectrical energy supplier. The Asian continent has 43 airports, and there are 5 airports solarpower plants in Indonesia. Most of the solar power plant uses an on-grid system